1968
DOI: 10.1080/15421406808082932
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Crystalline Methylchloromethane Compounds

Abstract: Polymorphism of the methylchloromethane compounds, (CH3),CC14-,, where n varies from 0 to 4, has been studied using lowtemperature X-ray diffraction techniques. Single crystals of both high and low-temperature phases were grown and crystal data were obtained for the various phases. The crystal structure of the phase of t-butyl chloride which is stable between -54 and -90" was determined. On the basis of the present investigation, the conclusion is reached that the hightemperature modifications are dynamically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

1973
1973
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 24 publications
1
52
0
1
Order By: Relevance
“…The data for the melting of 2-methylpropanol-2 agree with results given in the literature [7], No data for the pressure dependence of the melting of 2,2-dimethylpropionitrile and 2,2-di methylpropane were found in the literature, and also the pressure dependence of the solid-solid tran sition between the brittle hexagonal low tempera ture phase of 2,2-dimethylpropane and the plastic face centred cubic phase [8] appears to be unknown.…”
Section: Resultssupporting
confidence: 79%
“…The data for the melting of 2-methylpropanol-2 agree with results given in the literature [7], No data for the pressure dependence of the melting of 2,2-dimethylpropionitrile and 2,2-di methylpropane were found in the literature, and also the pressure dependence of the solid-solid tran sition between the brittle hexagonal low tempera ture phase of 2,2-dimethylpropane and the plastic face centred cubic phase [8] appears to be unknown.…”
Section: Resultssupporting
confidence: 79%
“…An early report (6) indicated that the mobility in solid n-hexane at -30" below the melting point was at least five times greater than that expected for electrons in the liquid a t the melting point. Neopentane would be a better candidate for study because electron mobility in the liquid is relatively high (9) and the material forms a plastic crystal (11) rather than a rigid solid upon freezing. Both of these properties increase the probability of obtaining a measurable electron conductance signal in the solid.…”
mentioning
confidence: 99%
“…Pentaerythritol, C(CH2OH)4, has been shown to undergo a transition at 452.7°K (Nitta & Watanab6, 1938) to just such a phase. As part of our attempts to define the sphericity of the molecular envelope that is required in order for plastic crystals to form (Rudman & Post, 1968;Rubin & Rudman, 1973), a series of substituted pentaerythritol compounds was selected for investigation.…”
mentioning
confidence: 99%